Petrology of ultramafic rocks at DSDP Holes 82-556, 82-558, and 82-560 - Peter Michael; Enrico Bonatti (PANGAEA, 1985)
Strongly serpentinized peridotites occur at shallow crustal levels at DSDP Sites 556 (35-Ma-old crust), 558 (35-Maold crust), and 560 (12-Ma-old crust) in the North Atlantic. Primary peridotite silicate minerals are preserved only at Sites 556 and 558, but all three sites have primary spinel preserved. The serpentinites at all three sites were probably spinel harzburgite tectonites, with little or no clinopyroxene. For orthopyroxene from Site 556, Mg/(Mg+Fe) ratios average 0.904, and Al2O3 contents are about 2.0-3.3 wt.%. Compositions of pyroxene-derived bastites from Sites 558 and 560 suggest that the original pyroxenes were probably low-alumina orthopyroxene. Spinels from all three sites have low Fe3+ and TiO2. Spinels from Sites 556 and 560 have high Cr/(Cr+Al) (0.45-0.53). Those from Site 558 have Cr/(Cr+Al) values that are among the highest measured for any plagioclase-free oceanic peridotites (0.55-0.62). Whole-rock chemistry, although affected by serpentinization, suggests that the peridotites had relatively low CaO, TiO2, Al2O3, and Na2O. Mineral and whole-rock chemistry and modal abundances suggest that Leg 82 peridotites are residua from partial melting, and that the extent of partial melting may have been greater in this region than farther south in the North Atlantic, or that the mantle was originally more depleted here.
Supplement to: Michael, P; Bonatti, E (1985): Petrology of ultramafic rocks from Sites 556, 558, and 560 in the North Atlantic. In: Bougault, H; Cande, SC; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 82, 523-528, https://doi.org/10.2973/dsdp.proc.82.129.1985